Cross-Sectional Relationship between Carotid-Femoral Pulse Wave Velocity and Biomarkers in Vascular-Related Diseases - Jinbo Liu; Kuanting Wang; Huan Liu; Hongwei Zhao; Wei Huang; Na Zhao; Lihong Li; Hongyu Wang (International Journal of Hypertension)
Objectives. The present study was done to investigate the relationship between carotid-femoral pulse wave velocity (CFPWV) and biomarkers such as homocysteine (Hcy), N-terminal pro-brain natriuretic peptide (NT-proBNP), and urine albumin (microalbumin) (UAE) in vascular-related diseases. Methods. 656 subjects were enrolled into our study. There were 377 patients with hypertension, 231 with coronary heart disease, 154 with diabetes mellitus, and 186 healthy subjects. They were divided into four groups according to the number of suffered diseases: group 1 had only one of three diseases, group 2 had two, and group 3 had all of three diseases. CFPWV was measured by Complior apparatus. Results. CFPWV was significantly higher in group 3 than in the healthy group, group 1, and group 2 (12.71 ± 2.38 vs 10.11 ± 2.28, 10.70 ± 2.12, and 11.92 ± 2.55, all p<0.05). The level of Hcy was significantly higher in group1, group 2, and group 3 than in healthy subjects, respectively. Levels of Log NT-proBNP and Log UAE were significantly higher in group 3 than in group 1 (2.27 ± 0.4 vs 2.10 ± 0.4, 1.00 ± 0.65 vs 0.68 ± 0.56, both p<0.05). Positive correlation between CFWV and Hcy, Log UAE, and Log NT-proBNP was found in the entire study group (r = 0.109, 0.196, and 0.119, all p<0.05). Multivariate analysis showed that pulse pressure, age, fasting plasma glucose, diastolic blood pressure, body mass index, and Log UAE were independent associating factors of CFPWV in all subjects (β = 0.334, p<0.001; β = 0.333, p<0.001; β = 0.126, p=0.004; β = 0.137, p=0.003; β = −0.142, p=0.002; and β = 0.098, p=0.031). Conclusions. CFPWV was significantly higher in subjects with hypertension, CHD, and DM. There was correlation between CFPWV and biomarkers such as NT-proBNP, Hcy, and urine albumin (microalbumin).